2022
DOI: 10.1021/acs.est.1c05326
|View full text |Cite
|
Sign up to set email alerts
|

Contribution, Composition, and Structure of EPS by In Vivo Exposure to Elucidate the Mechanisms of Nanoparticle-Enhanced Bioremediation to Metals

Abstract: Bacterial extracellular polymeric substances (EPS) have been recently found to contribute most for metal removal in nanoenhanced bioremediation. However, the mechanism by which NPs affect EPS–metal interactions is not fully known. Here, Halomonas sp. was employed to explore the role of EPS after in vivo exposure to Cd/Pb and polyvinylpyrrolidone (PVP) coated iron oxide nanoparticles (IONPs, 20 mg L–1) for 72 h. Cd–IONPs produced the highest concentrations of EPS proteins (136.3 mg L–1), while Cd induced the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…The blastp search against the SwissProt database identified in both MAGs the genetic basis for exopolysaccharide (EPS) biosynthesis, which may not only facilitate PAH degradation by enhancing the efficiency of all abovementioned PAH-degrading enzymes (Gutierrez et al, 2013;Alaba et al, 2018), but also confer metal-binding properties contributing to explain the observed ability of these strains to resist to and to sequester HMs (Amoozegar et al, 2012;Gupta and Diwan, 2017;Cao et al, 2022;Cheng et al, 2022). Specifically, a UDP-glucose 4-epimerase (e-value 0, score 1709, 97% identity), a UDP-glucose pyrophosphorylase (e-value 7.5 e − 180 , score 1300, 90% identity), and a poly-beta-1, 6-N-acetyl-D-glucosamine synthase (e-value 0, score 2011, 81% identity) were identified in A. xenomutans strain SRM1, with the latter two also present in H. alkaliantarctica strain SRM2 (respectively, e-value 2.6e − 165, score 1206, identity 77.3%, and e-value 0, score 1977, identity 86.1%).…”
Section: Genetic Basis For Hms Removal/detoxificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The blastp search against the SwissProt database identified in both MAGs the genetic basis for exopolysaccharide (EPS) biosynthesis, which may not only facilitate PAH degradation by enhancing the efficiency of all abovementioned PAH-degrading enzymes (Gutierrez et al, 2013;Alaba et al, 2018), but also confer metal-binding properties contributing to explain the observed ability of these strains to resist to and to sequester HMs (Amoozegar et al, 2012;Gupta and Diwan, 2017;Cao et al, 2022;Cheng et al, 2022). Specifically, a UDP-glucose 4-epimerase (e-value 0, score 1709, 97% identity), a UDP-glucose pyrophosphorylase (e-value 7.5 e − 180 , score 1300, 90% identity), and a poly-beta-1, 6-N-acetyl-D-glucosamine synthase (e-value 0, score 2011, 81% identity) were identified in A. xenomutans strain SRM1, with the latter two also present in H. alkaliantarctica strain SRM2 (respectively, e-value 2.6e − 165, score 1206, identity 77.3%, and e-value 0, score 1977, identity 86.1%).…”
Section: Genetic Basis For Hms Removal/detoxificationmentioning
confidence: 99%
“…Examples of this synergistic approach include microbial secretion -under mixed PAHs and HMs contamination -of enzymes with useful bioremediation activities (Chen et al, 2020) and of extracellular polysaccharides (EPSs). EPSs are particularly relevant targets for bioremediation studies, as they consist of a wide array of polymers and functional groups, that can simultaneously bind metals (thus enhancing HM extraction/removal from contaminated matrices) (Amoozegar et al, 2012;Ates, 2015;Little et al, 2014;Mohite et al, 2017;Gupta and Diwan, 2017;Cao et al, 2022;Cheng et al, 2022), and increase PAH solubilization and enzymatic degradation efficiency (Gutierrez et al, 2013;Alaba et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…96 Thus, EPS can change the environmental behaviour of NPs and might subsequently influence their fate and toxicity in the environment. 39…”
Section: Environmental Transformations Of Mnps In Freshwatermentioning
confidence: 99%
“…96 Thus, EPS can change the environmental behaviour of NPs and might subsequently influence their fate and toxicity in the environment. 39 In addition to the EPS derived from natural water, the biomolecules secreted by organisms could also interact with the MNPs' surface and form a new identity (i.e., eco-corona) which affects the stability and toxicity of the MNPs toward organisms in the surrounding environment. For example, a recent study showed that AuNPs could interact with protein secreted by D. magna and produce protein-corona, reducing the AuNP aggregation and potentially detoxifying AuNPs to D. magna by shielding their surface attraction.…”
Section: Biological Transformationsmentioning
confidence: 99%
See 1 more Smart Citation